Identification and assessment of the economic outcomes of commercial aircraft decommissioning: a theoretical and mathematical approach to support decision-making regarding endof-life aircraft treatment issues - Oliveira Junior, Flavio Soares de (2019)
This work develops the literature review on the problem of the end-of-life treatment of aircraft used for public passenger and cargo air transport in the context of international commercial aviation. The final destination decisions of these aircraft are analyzed from the point of view of the technical and economic aspects that guide the decision-making of the owners and operators of these production assets. In addition to the developed theoretical framework, a mathematical model for financial cost-benefit analysis is also proposed to assist in this decision-making process. The main objective is to determine the appropriate moment to take end-of-life treatment decisions for these aircraft, in order to ensure the recovery of value to the stakeholders.